Ocorrência, ecologia e conservação do guigó-da-caatinga (Callicebus barbarabrownae - Hershkovitz, 1990) - Ribeiro, Udemario Maia; Junior, José Monteiro do Nascimento; Barbosa, Francisco Mário Fagundes; dos Santos, Marcos Roberto Rossi (Neotropical Primates, 2020)
The blonde titi-monkey, Callicebus barbarabrownae - Hershkovitz 1990, is the only primate endemic to the Caatinga biome in northeastern Bahia. The species is threatened with extinction due to habitat loss, mainly caused by vegetation suppression and fragmentation of the forests in which they are found. The aim of the present study was to locate, with the aid of playback, and to record the fragments occupied by groups of titis in the city of Banzaê, Bahia, Brazil. In addition to documenting new occurrence localities, the use of fruits of the genera Capparis (Brassicaceae) and Manilkara (Sapotaceae) was described.